Biting midges of the Dasyhelea cincta group from Patagonia (Diptera: Ceratopogonidae) - Diaz, Maria Florentina (2009)
This revision of the Dasyhelea cincta group of biting midges in Patagonia recognizes two previously described species and a new species, Dasyhelea filiductus Díaz & Spinelli, from Argentinean Patagonia. Descriptions and illustrations are provided for all species as well as the pupa of D. cincta (Coquillett). Dasyhelea albopicta Ingram & Macfie is recognized as a junior synonym of D. cincta (Coquillett) and D. mediomunda Minaya is recorded for the first time from Argentina.